The fabulous imagination: on Montaigne's essays - Kritzman, Lawrence D. (Columbia Univ. Press, 2009)
Monster theory -- Montaigne's fantastic monsters and the construction of gender -- Representing the monster : cognition, cripples, and other limp parts in "Des boyteux" (III, 11) -- Death sentences -- Montaigne's fraternity : La Boétie on trial -- Montaigne on horseback, or, The simulation of death -- The anxiety of death : narrative and subjectivity in "De la diversion" (III, 4) -- Excavating Montaigne : the essayist on trial -- Philosophical impostures -- The Socratic makeover : the ethics of the impossible in "De la phisionomie" (III, 12) -- Romancing the stone : "De l'experience" (III, 13)